Literature Review: Formulation and Characterization of Nanoemulgel for Anticellulite Treatment - Ulayya, Hanidya Fidela; Erindyah Retno Wikantyasning (Universitas Muhammadiyah Surakarta, 2024)
Cellulite, a skin condition characterized by a dimpled, orange-peel appearance, commonly affects the thighs, abdomen, hips, and buttocks. Nanoemulgel, a combined system of nanoemulsion and gel, has gained attention as an effective topical drug delivery system, particularly for lipophilic drugs. This review examines the potential of nanoemulgel formulations in treating cellulite, focusing on their physical characteristics, drug delivery efficiency evaluated through skin penetration and anti-cellulite effects, specifically their ability to inhibit adipogenesis and reduce triglycerides. A total of 5 articles were selected for further review as they met the eligibility criteria, including nanoemulgel formulations containing active ingredients with potential anti-cellulite properties and in vitro or in vivo testing for anti-cellulite effectiveness. The results show that nanoemulgel formulations could be a new way to deliver lipophilic drugs to specific areas of the skin for treating cellulite.